Template Files:: The Holy Grail of Subtitling - Georgakopoulou, Panayota (Journal of Audiovisual Translation, 2019)
The use of English template files in workflows involving the multilanguage creation of subtitles from the same source audio assets, typically English, was one of the greatest innovations in the subtitling industry at the turn of the century. It streamlined processes, eliminated duplication of work, reduced direct costs, improved timelines and facilitated the quality control of large volumes of subtitle files whilst expanding the pool of available translators to complete the work. Template files set the basis for the globalisation of the subtitling industry and, almost two decades since their inception, they are still a topic of debate among language service providers and subtitlers. The present paper is a descriptive work, presenting a set of guidelines devised by the present author at the turn of the century, and used in practice for almost a decade in the production of multilingual subtitling work, enhanced and improved upon by the very subtitlers that worked with them. It aims at providing a reference point for debate to researchers in the subtitling field, so as to further the ongoing discussion on interlingual subtitling quality, practices and standards.